Estimating Genetic Variation Among Dent Corn Inbred Lines and Topcrosses Using Multivariate Analysis - Aydın, Nevzat; Gökmen, Sabri; Yıldırım, Ahmet; Öz, Ahmet; Figliuolo, Giovanni; Budak, Hikmet (My University, 2007)
Identification of suitable parental lines and high yielding hybrids in maize breeding and genetics program is crucial. The aims of this research were to: (1) determine the genetic variation between dent corn inbred lines from diverse backgrounds and topcrosses created by crossing each inbred line with the tester line 'FrMo 17', by using multivariate analyses, and (2) identify appropriate parents and topcrosses for future breeding and genetics program. Field evaluations were conducted in two different environments, Samsun and Tokat, during 2001-2002 growing season. Tasseling time, plant height, ear height, ear length, row number per ear,grain number per ear, single ear yield, 1000 grain weight and total grain yield were evaluated. Based on the field evaluation results,inbred lines, H49, Y582A and Yildiz32, had relatively high yielding genotypes when compared to the other genotypes, yet their combining ability with the tester line was low. The topcrossess developed by using Akpinar55 and Yildiz32 genotypes with the tester line was also identified as relatively high yielding genotypes. The most similar inbred lines, revealed by D multivariate distances, were B 87 and Pool 30a, while the topcrosses 496 x FrMo 17 and 504 x FrMo 17 were the most similar. On the other hand, the most different inbred lines were FrMo 17 and Pool 30 whereas the topcrosses were Pa.401.P x FrMo 17 and Akpinar 10 x FrMo 17. The inbreds Akpinar 55 and Yildiz32 wiirbe used in maize genetics and breeding programs as parents.
Keywords: Biyoloji